Impacts of Foreign Direct Investment on Economic Growth of Bangladesh: An Econometric Exercise - Dey, Sudip; Awal, Badrul Hasan (Asian Business Review, 2017)
Economic Growth is a concerning issue for the development of Bangladesh. Foreign direct investment (FDI) is a potential weapon for economic development, especially for Bangladesh. It can help us to build up physical capital, decrease unemployment rate, increase production capacity and create a good economic relationship between the domestic economies with global economy. This study examines the impacts of foreign direct investment on economic growth in Bangladesh during the period of 1990-2015 using Ordinary Least Square (OLS) method. The findings of the study reveal that FDI has its negative sign, which indicates that there is an inverse relationship between FDI and economic growth. The negative sign of FDI supports that Bangladesh should attract FDI increasing human capital, creating a good political environment and enhancing adequate infrastructure facilities, which will improve our economic growth.
Keywords: Economic Growth; Remittance; FDI; Export; Import; Inflation; Multiple regression; Multi-national companies